Sort by

- Relevance
- |Time

...4 +

**k**==>**k**= 380 - 120 = 260 verify: when y = 460, x = 800 so 460 = 800/4 +**k**==>**k**= 460 - 200 = 260 So**C**(x) = (x/4) + 260 increase in cost per mile is 0.25 dollars1 Answers · Science & Mathematics · 05/02/2020

Last answer first: Since

**k**does not depend on n, then 1/(2k)! can be factored out of the series...1 Answers · Science & Mathematics · 25/11/2019

... are in standard form Ax + By +

**C**= 0 .. so the slope is automatically -B/A 6x...opposite reciprocal or -1/(-1/2) or 2 4x-Ky=6 ... slope =**K**/4 = 2 ... so**K**= 85 Answers · Science & Mathematics · 04/11/2019

...14 25 15 8 16 17 17 0 18 9 19 18 20 1 21 10 22 19 23 2 24 11 25 20 26 3

**C**= (9p+3) -26k where**k**is based how big (9p+3) D(**C**) = (aC + b) -26k...1 Answers · Science & Mathematics · 12/10/2019

... of n people chosen

**k**at a time.**C**(n,**k**) = n! / (**k**! (n-**k**)!)**C**(10,3) = 10! / (3! 7!) = 120 I have trouble remembering the formula, so...4 Answers · Science & Mathematics · 07/10/2019

... with widths of 1/n and heights of f(

**k**/n), where**k**is some integer from 1 to n int(x^15 * dx , x = 0 , x = 1) (1/16) * x^16 +**C**(1/16) * (1^16 - 0^16) => (1/16) * 1 => 1/16 https://www.wolframalpha.com...2 Answers · Science & Mathematics · 19/09/2019

... general formula for exactly

**k**successes is: P(X =**k**) =**C**(n,**k**) * p^**k*** q^**k**n : number of trials (e.g. 5 flips)**k**...1 Answers · Science & Mathematics · 14/09/2019

h = kt+

**c**at t=0, h = 2500 m slope =**k**= –150 m/min h = –150t+**c**2500 = –150•0 +**c****c**= 2500 therefore equation is h = –150t + 2500 meters1 Answers · Science & Mathematics · 11/09/2019

...n -

**k**)!**k**!] That would mean:**C**(n, n -**k**) = n! / [(n - (n-**k**))! (n -**k**)!]**C**(n, n -**k**) = n! / [**k**! (n -**k**)!]**C**(n, n -**k**) = n! / [(n -**k**)!**k**!] Hence...6 Answers · Science & Mathematics · 12/09/2019

(x - h)^2 + (y -

**k**)^2 = r^2 (6 - h)^2 + (5 -**k**)^2 = r^2 (-3 - h)^2 + (2 -**k**)^2 = r^2 (-2 - h)^2 + (1 -**k**)^2 = r^2 (6 - h)^2 + (5 -**k**)^2 = (-3 - h...6k = 0 48 - 18 - 6k = 0 30 - 6k = 0 6k = 30**k**= 30/6**k**= 5 (6 - 1)^2 + (5 - 5)^2 = r^2...2 Answers · Science & Mathematics · 09/09/2019